REMEDIASI MENGGUNAKAN SCAFFOLDING BERBANTUAN ALGEBRAIC EXPERIENCE MATERIALS DI MTs DARUL AMIN PONTIANAK - Fitriani, Yenni; Jamiah, Yulis; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is want to know the effectivity of remediation using scaffolding and supported with Algebraic Experience Materials to improve concept comprehension and student’s learning outcomes in materials of addition and subtraction of the student in class VII of MTs Darul Amin Pontianak. Research method used is analysis descriptive and the form is case study. The subject of this research is 17 students in class VII MTs Darul Amin Pontianak that had scores below minimum completeness criteria based on the result of pre-test in material of algebraic addition and subtraction. The result of pre-test showed the students had problems in the lack of understanding for integers and differentiation of like terms dan unlike terms. Data analysis result showed remediation using scaffolding and supported with Algebraic Experience Materials was unable to improve student’s concept comprehension as a whole, but still improved based the result of post-test. The calculations using Effect Size formula to know the effectivity, the result was 0,42 which fell in the category moderate, so remediation using scaffolding and supported with Algebraic Experience Materials can be used as learning strategy of this material.Keywords : Remediation, Scaffolding, Algebraic Experience Materials